The Students Perception toward the Use of Cooperative Integrated Reading Composition in Teaching Reading Report Text - Noerkhalifah, Annisa; WIjayatiningsih, Testiana Deni; Mulyadi, Dodi (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Reading skill is very important for students who mostly learn English through written text. They need some models from the teacher in comprehending reading text especially report text. This condition happened in SMA Negeri 1 Gubug. They still needed some models and attractive method in comprehending report text. They also felt less motivated and noisy when they read a text without any attractive activities. Therefore, this research is focused on the analysis of students âperception using Cooperative Integrated Reading Composition in teaching reading report text. The method used in this research was descriptive qualitative one. It used questionnaire as the data collection. The results of this research showed that the studentsâ perception in reading report text using Cooperative Integrated Reading Composition had good responses and they joined the discussion enthusiastically. To sum up, the use of Cooperative Integrated Reading Composition gives a good impact for the studentsâ reading ability viewed from their perception.